1990
DOI: 10.1161/01.cir.81.6.1899
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and immunopathological consequences of active immunization of spontaneously hypertensive and normotensive rats against murine renin.

Abstract: Spontaneously hypertensive Okamoto-strain rats (SHR) and normotensive Wistar-Kyoto (WKY) rats were actively immunizedwith mouse renin to investigate the effect on blood pressure of blocking the renin-angiotensinogen reaction. Ten male SHR and 10 male WKY rats were immunizedwith purified mouse submandibular gland renin. Control rats were immunized with bovine serum albumin. Antirenin antibodies were produced by both SHR andWKY rats, but renin-immunized SHR had higher titers of circulating renin antibodies after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…26 It is interesting to compare the results of the present study with those from the study on renin immunization in SHR. 7 The hemodynamic and the biochemical responses to renin immunization, Ang II antagonism or ACE inhibition are quite comparable, indicating that the major effects of the immunization were due to the inhibition of renin and not to the renal disease. Plasma urea concentrations were significantly increased in the immunized rats, whereas neither DuP 753 nor benazeprilat had any effects on plasma urea or creatinine concentrations.…”
Section: -21mentioning
confidence: 93%
See 2 more Smart Citations
“…26 It is interesting to compare the results of the present study with those from the study on renin immunization in SHR. 7 The hemodynamic and the biochemical responses to renin immunization, Ang II antagonism or ACE inhibition are quite comparable, indicating that the major effects of the immunization were due to the inhibition of renin and not to the renal disease. Plasma urea concentrations were significantly increased in the immunized rats, whereas neither DuP 753 nor benazeprilat had any effects on plasma urea or creatinine concentrations.…”
Section: -21mentioning
confidence: 93%
“…7 The interpretation of this study is complicated by the development of an autoimmune disease of the kidney. Nevertheless, other recent studies have shown that blood pressure is lowered in SHR after acute administration of novel compounds blocking the RAS at levels other than ACE.…”
Section: âmentioning
confidence: 98%
See 1 more Smart Citation
“…8 The efficacy of interrupting the renin-angiotensin system in SHR is difficult to explain, because SHR do not have elevated plasma renin activity or elevated plasma angiotensin II (Ang II) concentrations relative to their normotensive counterpart, the Wistar-Kyoto (WKY) rat. A possible explanation for the efficacy of interrupting the renin-angiotensin system in SHR, despite normal plasma renin activity, may be that SHR have a more active vascular renin-angiotensin system than WKY rats.…”
Section: T He Spontaneously Hypertensive Rat (Shr) Ismentioning
confidence: 99%
“…9 Further studies showed that anti-renin vaccines caused a significant and sustained decrease in BP, but could also induce autoimmune renal disease in animal models. 10 A vaccine against Ang I was tested in a phase IIa clinical trial, and was found to be safe, but did not effectively cause a decrease in BP in patients with essential hypertension. 11 In contrast, the study by Tissot et al 8 using a vaccine against Ang II showed a small, but significant, decrease in both systolic and diastolic BP in patients with mild-to-moderate hypertension.…”
Section: Introductionmentioning
confidence: 99%